Corporate Social Responsibility in Business-to-Business Markets: How Organizational Customers Account for Supplier Corporate Social Responsibility Engagement - Homburg, Christian and Stierl, Marcel and Bornemann, Torsten (Journal of Marketing, 2013)
Despite the high relevance of corporate social responsibility (CSR) in current business practice and the considerable research on CSR outcomes in consumer markets, investigations of its influence on organizational business relationships are scarce. Relying on instrumental stakeholder theory, the authors develop and empirically test a framework of the influence of a supplier's CSR engagement on organizational customer outcomes. Findings from an examination of 200 cross-industry supplier–customer dyads reveal positive effects of two facets of a supplier's CSR efforts on customer loyalty through distinct mechanisms. Business practice CSR fosters customers' trust, whereas philanthropic CSR strengthens customer–company identification. The authors distinguish a supplier's actual CSR engagement and customers' perception of these CSR activities. In addition, they consider central contingency factors reflecting uncertainty and dependence in business-to-business relationships that determine the effectiveness of CSR.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUwOS9qbS4xMi4wMDg5